Constrction of data driven-centric smart home intelligent operating system - Zheng WEI; Weijia SHI; Zhengkai ZHANG (Dianxin kexue)
From the background of the second half of the internet era,when constructing the smart home intelligent operating system,data-driven should be the foundation,and data evaluation should be the means.By using accurate and efficient data collection methods,the smart home intelligent operating system which adapted the development of future 5G,internet of things and artificial intelligence and other technology was built.Firstly,the characteristics and trends of the smart home business was introduced,and then the opinion of data was the foundation of smart home operation was explained.Finally,the future of data and smart home operation was introduced.